PENERAPAN PSIKOLOGI KOMUNIKASI DALAM PENYAMPAIAN PESAN DAKWAH - Wahid, Lalu Abdurrachman (Universitas Islam Negeri Mataram, 2021)
The application of communication psychology in delivering da’wah messages in the Al-Qur’an education park is very important because by applying psychology when conveying information to others, it will make information easier to understand so that the communication process runs more effectively. The research method used in this research is qualitative with descriptive type field research. The results showed that TPA As-Syifa has applied the science of communication psychology in the delivery of his da’wah messages. Then the da’wah method applied at the As-Syifa TPA is the bi-lisan da’wah method, bil-qalam da’wah, and the bil-hal da’wah. Further findings regarding the application of communication psychology in the delivery of da’wah messages at TPA As-Syifa use the da’wah method with effective communication techniques and da’wah method with persuasive communication techniques.